16th IEEE Symposium on Computer Arithmetic, 2003. Proceedings.
DOI: 10.1109/arith.2003.1207654
|View full text |Cite
|
Sign up to set email alerts
|

High-performance left-to-right array multiplier design

Abstract: We propose a split array multiplier organized in a left-to-right leapfrog (LRLF) structure with reduced delay compared to conventional array multipliers. Moreover, the proposed design shows equivalent performance as tree multipliers for n ≤ 32. An efficient radix-4 recoding logic generates the partial products in a left-to-right order. The partial products are split into upper and lower groups. Each group is reduced using [3:2] adders with optimized signal flows and the carry-save results from two groups are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…In the TP implementation made in MB, [2] adopts modified booth encoder and decoder are shown in Figure 2(a) & (b). Different methodologies of implementing MB recoding logic are explained in [13,14].…”
Section: Tp Implementation In Modified Boothmentioning
confidence: 99%
“…In the TP implementation made in MB, [2] adopts modified booth encoder and decoder are shown in Figure 2(a) & (b). Different methodologies of implementing MB recoding logic are explained in [13,14].…”
Section: Tp Implementation In Modified Boothmentioning
confidence: 99%
“…Huang and Ercegovac [8] presented the arithmetic details about the signal gating schemes and showed 10% to 45% power reduction for adders. The combination of the Signal Flow Optimization (SFO), left-to-right leapfrog structure, and upper/lower split structure was incorporated in the design to optimize the array multipliers by Huang and Ercegovac [9] and it is reported that the new approach can save about 20% power dissipation. Wen et al [10] reported that for the known output, some columns in the multiplier can be turned off and it reduces 10% power consumption for random inputs.…”
Section: Mmadheswaran Professor Department Of Ece Muthayammal Enginmentioning
confidence: 99%
“…Finally, other techniques to optimize multiplication focus on fine-grained manipulations that are suitable for ASIC or custom implementations [22][23][24] [25]. However, because FPGAs are multipurpose devices, they must support more general multiplication structures.…”
Section: Related Workmentioning
confidence: 99%